The Variation of The Designing in decorative the Calligraphic authorization: حسـين علي يونــس (Al-Academy, 2016)
Formed a decoration element Tzeigna important holidays linear, since regulating mechanism of vocabulary and formative elements Btnoatha through activation design with space linear in order to add value expressionistic, and achieve career goals and aesthetic, has promised these diversities and one of the finest artistic achievements that excelled the designer patterned through expertise and skill in the output of the design artwork beautiful image to fit with the importance degree in the field of calligraphy and set the rules, and was questionably basic research problem is the following: What are the variations in the design of linear motifs Vacations? In order to solve these problems and to reach the desired outcomes research aims to detect variations in the design of linear motifs Vacations, set by the researcher Macs that have emerged In Iraq and Turkey, within a period determined by the year (1268 AH 0.1852 m), and up to (1430 -2010 AD). Dealt with the theoretical framework the following topics; and origination Vacations linear evolution, and variations decorative holiday linear, and the foundations of building designs in decorative holiday, and public space design motifs, and the diversity of design boards leave sin, has also been studying the diversity of units formative in decorative design. The third chapter devoted to display the search procedures, which included his community on the boards Vacations linear ornate kinds and which numbered (40) model, researcher selected ones specimens intentionality and of (4) models, accounting for (10%) of the community overall, has Follow the descriptive analytical method, using the instrument whose form for analysis, which was built on several axes, and presented to the experts to ensure their validity, and achieve goals. The fourth chapter evolved to include the results of which: that diversity phenotypic to form frames decorative add versatile Last implicitly with the overall design on according to the compatibility between the shapes and elements that make up the overall design., And a variety of spaces because of the diversity of sites occupancy and thus the diversity of designs approved in organized Vatceft mostly in color dark This is due to the spaces characterized by linear light colors. And the adoption of a particular division to design a symmetrical or asymmetrical design space given various options through a variety of motifs occupancy within the space in a uniform manner.